The influence of social capital on opportunity emergence and exploitation: A comparison of portfolio and serial entrepreneurs - Christian Lechner; Florian Kirschenhofer; Michael Dowling (Journal of Innovation and Entrepreneurship, 2016)
Habitual entrepreneurs are a frequent and important phenomenon in entrepreneurship and for the economy. We lack, however, a systematic understanding of the advantages or disadvantages of multiple business ownership and specifically if portfolio and serial entrepreneurs are different in detecting and exploiting opportunities. Research on habitual entrepreneurs has mainly focused on a human capital and an organizational perspective. In order to further advance our understanding of habitual entrepreneurship, we conducted a case study research focusing on the social capital of habitual entrepreneurs and on how, by investigating differences between serial and portfolio entrepreneurs, it is related to the emergence and exploitation of opportunities.
Keywords: L26; 650; Entrepreneurship